2019
DOI: 10.3390/catal9030218
|View full text |Cite
|
Sign up to set email alerts
|

K-Modulated Co Nanoparticles Trapped in La-Ga-O as Superior Catalysts for Higher Alcohols Synthesis from Syngas

Abstract: Owing to the outstanding catalytic performance for higher alcohol synthesis, Ga-Co catalysts have attracted much attention. In view of their unsatisfactory stability and alcohol selectivity, herein, K-modulated Co nanoparticles trapped in La-Ga-O catalysts were prepared by the reduction of La1−xKxCo0.65Ga0.35O3 perovskite precursor. Benefiting from the atomic dispersion of all the elements in the precursor, during the reduction of La1−xKxCo0.65Ga0.35O3, Co nanoparticles could be confined into the K-modified La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Moreover, the higher alcohols, after separation and purification, can serve as feed stocks for value-added fine chemicals, demonstrating a wide application prospect [4]. Generally, the catalytic production process for higher alcohols synthesis from syngas needs to occur over the solid catalysts, which are roughly classified into the following four categories: modified methanol synthesis catalysts [5,6], modified Fischer-Tropsch synthesis catalysts [7,8], noble metal ruthenium-based catalysts [9,10], and molybdenum sulfide-based catalysts [11,12]. Among these catalyst systems, the modified methanol synthesis catalyst mainly produced methanol with a lower C 2+ OH selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the higher alcohols, after separation and purification, can serve as feed stocks for value-added fine chemicals, demonstrating a wide application prospect [4]. Generally, the catalytic production process for higher alcohols synthesis from syngas needs to occur over the solid catalysts, which are roughly classified into the following four categories: modified methanol synthesis catalysts [5,6], modified Fischer-Tropsch synthesis catalysts [7,8], noble metal ruthenium-based catalysts [9,10], and molybdenum sulfide-based catalysts [11,12]. Among these catalyst systems, the modified methanol synthesis catalyst mainly produced methanol with a lower C 2+ OH selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [130] show that employing LaCoyGa1-yO3 mixed oxides as catalysts, alcohols (mostly methanol/ethanol) may be synthesized from syngas. The precursor of segregated cobalt nanoparticles in the LaGaO composite oxide is La1-…”
Section: Coxfe1-xoy Catalyst For Co2 Hydrogenationmentioning
confidence: 99%
“…They claimed that the development of homogeneous and highly dispersed Rh–Fe alloys was decisive toward the high selectivity and activity of YRh 0.5 Fe 0.5 O 3 /ZrO 2 . In another similar work by Liu et al, K-modulated Co nanoparticles trapped in La–Ga–O catalysts were synthesized by reducing the La 1– x K x Co 0.65 Ga 0.35 O 3 perovskite precursor. It was found that adding K improved Co dispersion and provided metallic Co as additional electron donors, leading to high activity and superior selectivity to higher alcohols.…”
Section: Introductionmentioning
confidence: 99%